Crocodile tear syndrome treated with lacrimal gland incobotulinum toxin A injection: a case series - Krivda, Kathleen; Clabeaux, Carson; Yakopson, Vladimir (Digital Journal of Ophthalmology, 2023)
Crocodile Tear Syndrome (CTS) is a late complication of Cranial Nerve VII (CNVII) palsy characterized by unilateral lacrimation in response to gustatory stimulation. We present a retrospective case series of two patients who were diagnosed with Crocodile Tear Syndrome after recovering from unilateral idiopathic Cranial Nerve VII (CNVII) palsy. Both patients received transconjunctival lacrimal gland Incobotulinum toxin A (INCO BTX-A, Xeomin®) injection, with dosage range from 5- 16 units (U). Outcomes were measured by treatment efficacy and adverse drug effects. Both patients reported resolution of gustatory lacrimation post treatment. The patient who was treated with 16U experienced transient ptosis and diplopia following injection. While the patient treated with 5-7.5 U experienced no adverse effects. We conclude that transconjunctival lacrimal gland INCO BTX-A injection is efficacious treatment for CTS. Utilizing lower doses of botulinum toxin may have a more favorable side effect profile.